REGIONAL DEVELOPMENT EFFORTS THROUGH ECONOMIC EMPOWERMENT OF THE JABUNG DISTRICT COMMUNITY - Hermanda, Agus Iprah; Hafifah, Wardatul; Murotul, Fatma Kana (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2024)
This research entitled "Efforts to Develop Regional Through Economic Empowerment of Jabung Subdistrict Community Through Cow's Milk Production" aims to find out how regional development efforts are carried out through economic empowerment in the community. Development is a transformation or change from a certain condition to a better condition. With regard to government social assistance, progress can be defined as work to improve or work on local government assistance. As we may be aware, rural communities cannot be distinguished from underdevelopment, despite the fact that rural communities have a lot of potential.Research conducted by the author who took the object of research on the Agro Niaga Cooperative where the existence of cooperatives greatly affects the economy of local residents. The presence of KAN can be proven by the impact of the creation that can be felt both by the surrounding area and to KAN itself. KAN Jabung is one of the cooperatives that participates in the management of various cooperative in Indonesia, specifically in administration monetary through reserve fund arrangements and advance administration, dairy, horticulture and general stores for individuals. The ability of KAN as an effort to move the regional economy is also highly expected in the progress of the community's economy. His presence should have an option to help the economy. The economy in general favors the lower working class (poor) and cooperatives are seen as something that is ready to fight for the economic needs of the community. as stated in Article 3 of Government Regulation No.25 of 1992 concerning Cooperatives.